2022
DOI: 10.1101/2022.02.24.22271483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma metabolomics of primary open-angle glaucoma in three prospective US cohorts and the UK Biobank

Abstract: Purpose: To better understand the etiologic pathways in glaucoma, we aimed to identify pre-diagnostic plasma metabolites associated with glaucoma risk. Methods: In a case-control study from the Nurses Health Study (NHS), NHSII and Health Professionals Follow-Up Study (HPFS), 599 incident primary open-angle glaucoma (POAG) cases (mean time between blood draw and diagnosis was 10.3 years) were 1:1 matched to 599 controls. Plasma metabolites were measured with LC-MS/MS at the Broad Institute (Cambridge, MA, USA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Hyperlipidemia is associated with an increased risk of elevated IOP and glaucoma with poor mechanistic understanding (5,6,73,74). Systemic cholesterol levels are closely related to glaucoma occurrence and IOP elevation (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is associated with an increased risk of elevated IOP and glaucoma with poor mechanistic understanding (5,6,73,74). Systemic cholesterol levels are closely related to glaucoma occurrence and IOP elevation (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while HDL and LDL have opposing associations in the case of cardiovascular diseases, with higher LDL associated with a higher disease risk, and higher HDL associated with a lower risk, the aforementioned data showed instead that both HDL and LDL were positively associated with IOP, thus suggesting that the pathway mediating the relationship between lipids metabolism and IOP is different compared to the one that mediates cardiovascular risk 28 . Further research investigating metabolite profiles in multiple cohorts including both the UK Biobank and US cohorts confirmed these results, indicating the importance of serum lipids in glaucoma pathophysiology with the potential for future development of drugs targeting lipid metabolism 29 …”
Section: Lifestyle/modifiable Risk Factors For Glaucomamentioning
confidence: 98%
“…One great advantage of the UK Biobank is that it includes detailed eye measurements recorded for over 100,000 participants, including intraocular pressure (IOP) determined with the Ocular Response Analyzer and macula region inner retinal thickness values assessed with OCT. The UK Biobank allowed over the years multiple milestone discoveries in the field of glaucoma, including the role of genetics and behavioral risk factors, 15–32 that have been discussed extensively during the Think Tank and will be summarized in detail later in the manuscript. For example, results from the UK Biobank provided insights on the determinants of IOP, the major known risk factor for glaucoma onset and progression: in a cross-sectional study on 110,573 subjects, systolic BP was found to have the strongest association with IOP (partial R 2 : Goldmann-correlated IOPg: 2.30%; corneal-compensated IOPcc: 2.26%) 15 .…”
Section: Big Data/data Sciencementioning
confidence: 99%
“…POAG was significantly linked to dysregulated fatty acid elongation and synthesis and the degradation of ketone bodies (40). Other studies have identified an adverse correlation between high levels of diglycerides and triglycerides and glaucoma (41) and the association of high total cholesterol levels and low HDL levels with glaucoma (42). When identifying the lipidomic profile of aqueous humour in open-angle glaucoma (OAG), Cabrerizo et al ( 43) reported a higher level of most diacylglycerophosphocholines and 1-ether, 2-acylglycerophosphocholines, 14 sphingomyelins, and 5 cholesteryl esters in OAG patients compared to controls.…”
Section: Metabolic Dysfunction In Glaucoma Is Not Constrained To Reti...mentioning
confidence: 99%